How Does COVID-19 Pandemic Impact on Incidence of Clostridioides difficile Infection and Exacerbation of Its Gastrointestinal Symptoms? - Azimirad, Masoumeh; Noori, Maryam; Raeisi, Hamideh; Yadegar, Abbas; Shahrokh, Shabnam; Asadzadeh Aghdaei, Hamid; Bentivegna, Enrico; Martelletti, Paolo; Petrosillo, Nicola; Zali, Mohammad Reza (Frontiers in Medicine, 2021)
Coronavirus disease 2019 (COVID-19) has rapidly spread all over the world with a very high rate of mortality. Different symptoms developed by COVID-19 infection and its impacts on various organs of the human body have highlighted the importance of both coinfections and superinfections with other pathogens. The gastrointestinal (GI) tract is vulnerable to infection with COVID-19 and can be exploited as an alternative transmission route and target for virus entry and pathogenesis. The GI manifestations of COVID-19 disease are associated with severe disease outcomes and death in all age groups, in particular, elderly patients. Empiric antibiotic treatments for microbial infections in hospitalized patients with COVID-19 in addition to experimental antiviral and immunomodulatory drugs may increase the risk of antibiotic-associated diarrhea (AAD) and Clostridioides difficile infection (CDI). Alterations of gut microbiota are associated with depletion of beneficial commensals and enrichment of opportunistic pathogens such as C. difficile. Hence, the main purpose of this review is to explain the likely risk factors contributing to higher incidence of CDI in patients with COVID-19. In addition to lung involvement, common symptoms observed in COVID-19 and CDI such as diarrhea, highlight the significance of bacterial infections in COVID-19 patients. In particular, hospitalized elderly patients who are receiving antibiotics might be more prone to CDI. Indeed, widespread use of broad-spectrum antibiotics such as clindamycin, cephalosporins, penicillin, and fluoroquinolones can affect the composition and function of the gut microbiota of patients with COVID-19, leading to reduced colonization resistance capacity against opportunistic pathogens such as C. difficile, and subsequently develop CDI. Moreover, patients with CDI possibly may have facilitated the persistence of SARS-CoV-2 viral particles in their feces for approximately one month, even though the nasopharyngeal test turned negative. This coinfection may increase the potential transmissibility of both SARS-CoV-2 and C. difficile by fecal materials. Also, CDI can complicate the outcome of COVID-19 patients, especially in the presence of comorbidities or for those patients with prior exposure to the healthcare setting. Finally, physicians should remain vigilant for possible SARS-CoV-2 and CDI coinfection during the ongoing COVID-19 pandemic and the excessive use of antimicrobials and biocides.